Problem solving in chemistry supported by metacognitive scaffolding: teaching associates' perspectives and practices. Issue 2 (15th February 2022) - Vo, Kimberly; Sarkar, Mahbub; White, Paul J.; Yuriev, Elizabeth
Abstract : Problem solving is a fundamental skill that chemistry graduates should possess, yet many students have difficulties solving problems in chemistry. These difficulties may be either student- or instructor-driven. Instructor-related difficulties could stem from some teaching practices, such as expecting students to apply procedures without requiring them to show their reasoning or solely focusing on worked examples. Such practices could inhibit the development of problem-solving skills. To address these challenges, our group developed a metacognitive scaffold (Goldilocks Help) to support both students and instructors through structured problem solving. This scaffold breaks down the problem-solving process into phases and places emphasis on reasoning required throughout that process. This study explored how teaching associates (TAs) used the problem-solving scaffold and how this practice affected their teaching and perceptions of student learning. Seven TAs based at a large research-intensive Australian university were interviewed, and the data were analysed using the framework approach. Teaching with the problem-solving scaffold was found to be beneficial, albeit with initial student resistance. The scaffold provided a common thinking structure between the TAs and students, enabling TAs to easily identify mistakes and address specific areas of concern. However, TAs also experienced students' attention shift from content to the scaffold. Initially, many students unproductively viewed the process as requiring two separate actions of solving the problem and being explicit about the problem-solving process they used, as opposed to an integrated activity. Through constant reinforcement and prompting by TAs during and prior to solving the problem, students continued to grasp how to effectively internalise the scaffold to assist their problem solving. Understanding how TAs use problem-solving scaffolds with students will add to the field of education research to inform innovations in supporting the development of students' problem-solving skills.